Strategi Meningkatkan Daya Saing dan Upaya Bertahan Saat Pandemi Covid 19 Pada Usaha Kecil dan Menengah PT Sasak Maiq Batu Layar Lombok Barat - Ida Bagus Eka Artika; Irianto Irianto; Ida Ayu Ketut Marini; Baiq Ertin Helmida (Valid: Jurnal Ilmiah, 2021)
The sustainability of PT Sasak Maiq, in West Lombok Regency, as one of the Small and Medium Enterprises has recently been threatened by the Covid - 19 pandemic which began to hit Indonesia in early 2020. PT Sasak Maiq is concerned about this because it has an impact on reducing turnover sales of their products. This requires a strategic study, to be able to maintain the existence of PT Sasak Maiq in the Covid-19 pandemic, which cannot be predicted when it will end. This research is a descriptive study with the aim of knowing which strategies are suitable to be applied in order to maintain the existence of PT Sasak Maiq in the future. The data is sourced from stakeholders, with an analysis technique in the form of environmental analysis (SWOT Analysis). The results showed that the suitable strategy to be applied to maintain the sustainability of PT Sasak Maiq is the ST strategy, which is in the form of a diversification strategy, by creating the new unique product, strengthening the online marketing network, maintaining a price strategy, maintaining relationships with marketing networks both at domestic and abroad, so that it can maintain demand for its products.